Effort-Reward Imbalance and Quality of Life Among Female Nurses at a General Hospital in Japan - Kikuchi, Yoko; Nakaya, Makoto; Ikeda, Miki; Narita, Kyoko; Takeda, Mihoko; Nishi, Miyoko (IntechOpen, 2012)
None